2015
DOI: 10.5455/ijmsph.2015.0000201448
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak investigation of typhoid fever in Pondicherry, South India, 2013

Abstract: Background: Preliminary investigation at Pediatric ward of Indira Gandhi Medical College revealed admission of a cluster of typhoid cases who were residents of one particular street in a nearby locality. Objectives: This study was undertaken to estimate the magnitude of the outbreak, identify the source of infection, and, thereby, institute control measures. Materials and Methods: An investigation team including 10 MBBS students carried out a sanitary survey, house-to-house survey, data collection using epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
(5 reference statements)
0
6
1
Order By: Relevance
“…Several outbreak investigations studies have been done in India where few studies are multifactorial, while most of them are concluding contaminated water to be the source of outbreak and clean water and hygienic measures had been proven to be effective. [ 3 4 8 9 10 11 12 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several outbreak investigations studies have been done in India where few studies are multifactorial, while most of them are concluding contaminated water to be the source of outbreak and clean water and hygienic measures had been proven to be effective. [ 3 4 8 9 10 11 12 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Typhoid fever is endemic in India. [ 7 ] There have been various outbreaks of typhoid fever reported from different parts of India including Pondicherry,[ 8 ] Maharashtra,[ 9 ] Bangalore,[ 10 ] Rajasthan,[ 11 ] and West Bengal. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Second, testing of water sources used by actual cases would have provided a stronger linkage between infection and water sources. Third, while this study has a larger sample size and more comprehensive set of water source types than previous environmental studies associated with outbreaks (10)(11)(12)(13)(14)(15), data from additional samples, especially from unprotected springs, wells, and taps, would have allowed a more robust analysis of water quality. Fourth, S. Typhi is difficult to culture from environmental samples; improved culture methods are needed.…”
Section: <1mentioning
confidence: 99%
“…Despite the high incidence of typhoid fever globally, relatively few outbreak investigations incorporate drinking water testing (10)(11)(12)(13)(14)(15) and routine water testing for S. Typhi is rarely done in regions where S. Typhi is endemic (16). While these studies have provided useful information, more comprehensive sampling and testing strategies are needed to identify drinking water sources that represent higher disease transmission risks and areas of focus for public health interventions.…”
mentioning
confidence: 99%
“…A World Health Organization study estimated the incidence and mortality rate to be 21.7 million and 217 000 cases annually . Typhoid fever outbreaks in Uganda, North India, South India, Songkhla, and Malawi‐Mozambique border in recent years suggested that the disease has yet to be eradicated. S .…”
Section: Introductionmentioning
confidence: 99%